2016
DOI: 10.1177/0003702816651891
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of the Intrinsically Disordered Protein p53 Using Raman Spectroscopy

Abstract: The intrinsically disordered protein p53 has attracted a strong interest for its important role in genome safeguarding and potential therapeutic applications. However, its disordered character makes difficult a full characterization of p53 structural architecture. A deep knowledge of p53 structural motifs could significantly help the understanding of its functional properties, in connection with its complex binding network. We have applied Raman spectroscopy to investigate the structural composition and the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 53 publications
1
39
0
Order By: Relevance
“…Figure shows the corresponding Raman spectrum from each specimen of p53 protein. Usually, the fingerprint region between 400 and 1,800 cm −1 provides the most useful information about the protein structure so that we extend the measurements to 300–2,000 cm −1 to observe a wider region . As expected, the vibrational spectra contain a complex set of peaks and overlapping bands, which cannot be used directly for structural determination; however, several studies have been carried out to investigate the Raman spectrum of individual amino acids, dipeptides, and tripeptides, whose results are useful for, based on frequency coincidences, assigning vibrations to the most prominent bands in the protein spectrum .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure shows the corresponding Raman spectrum from each specimen of p53 protein. Usually, the fingerprint region between 400 and 1,800 cm −1 provides the most useful information about the protein structure so that we extend the measurements to 300–2,000 cm −1 to observe a wider region . As expected, the vibrational spectra contain a complex set of peaks and overlapping bands, which cannot be used directly for structural determination; however, several studies have been carried out to investigate the Raman spectrum of individual amino acids, dipeptides, and tripeptides, whose results are useful for, based on frequency coincidences, assigning vibrations to the most prominent bands in the protein spectrum .…”
Section: Resultsmentioning
confidence: 99%
“…As expected, the vibrational spectra contain a complex set of peaks and overlapping bands, which cannot be used directly for structural determination; however, several studies have been carried out to investigate the Raman spectrum of individual amino acids, dipeptides, and tripeptides, whose results are useful for, based on frequency coincidences, assigning vibrations to the most prominent bands in the protein spectrum . Features observed in the wt p53 spectrum are closer with those previously reported by Signorelli et al, but in addition, we observed two prominent peaks in 416 and 480 cm −1 that could be assigned to the symmetric stretching band and are present in the mutants as well. For all p53 types, the dominant peak at 848 cm −1 and the shoulder in 825 cm −1 correspond to the scattering of aromatic amino acid Tyr.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…gemstone identication), 227 biology (e.g. secondary structure of polypeptides/proteins, phospholipids), [228][229][230][231] material science 232,233 (e.g. semiconductors, carbon materials and polymers) and life science (e.g.…”
Section: Afm and Raman Spectroscopytip-enhanced Raman Spectroscopy (Ters)mentioning
confidence: 99%